2023
DOI: 10.1186/s12902-022-01262-6
|View full text |Cite
|
Sign up to set email alerts
|

Association of hepatic/pancreatic iron overload evaluated by quantitative T2* MRI with bone mineral density and trabecular bone score

Abstract: Background Iron-overloaded patients are recognized as presenting an increased risk of osteoporosis. However, studies on the correlation between osteoporosis and organ iron overload are controversial or scarce. The aim of this study is to assess bone mineral density (BMD) and trabecular bone score (TBS) in correlation with hepatic and pancreatic iron overload. Methods Forty-one patients diagnosed with hemoglobinopathies, were studied. BMDs of the lu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…At present, many studies have shown that T 2 * /R 2 * relaxation quantitative methods have good linear correlation when measuring LIC at 1.5 T and 3 T. T 2 * is negatively correlated with LIC. R 2 * is positively correlated with LIC and has shown excellent agreement and reproducibility ( 1 , 4 , 5 , 22 , 23 , 27 , 29 ), and this measurement has become a reliable quantitative assessment of liver iron overload. Figure 1 from Xu et al ( 4 ) shows liver T 2 * measured by different software.…”
Section: Mri Examinationmentioning
confidence: 90%
See 3 more Smart Citations
“…At present, many studies have shown that T 2 * /R 2 * relaxation quantitative methods have good linear correlation when measuring LIC at 1.5 T and 3 T. T 2 * is negatively correlated with LIC. R 2 * is positively correlated with LIC and has shown excellent agreement and reproducibility ( 1 , 4 , 5 , 22 , 23 , 27 , 29 ), and this measurement has become a reliable quantitative assessment of liver iron overload. Figure 1 from Xu et al ( 4 ) shows liver T 2 * measured by different software.…”
Section: Mri Examinationmentioning
confidence: 90%
“…With SE and GRE sequences, based on the influence of iron, the transverse relaxation of proton magnetization in water becomes faster, resulting in attenuation of magnetic resonance signal intensity, and T 2 and T 2 * weighted imaging are obtained, respectively. Then the corresponding signal decay time constants T 2 and T 2 * and the corresponding relaxation rates R 2 (1,000/T 2 ) and R 2 * (1,000/T 2 * ) were obtained ( 1 , 3 , 22 ). Relaxometry is a quantitative assessment of MRI signal loss caused by the shortening of T 2 /T 2 * relaxation times ( 21 , 22 ).…”
Section: Mri Examinationmentioning
confidence: 99%
See 2 more Smart Citations
“…Patients who had less than one year of menopause, secondary osteoporosis, or recent use of medications that may affect bone metabolism (such as thiazolidinediones, immunosuppressants, systemic glucocorticoids, or hormone replacement therapy) were excluded. According to the standards of the World Health Organization (WHO) [15], the subjects were divided into three groups according to their BMD status: the normal group (T≥-1), the osteopenia group (-2.5 < T < -1) and the osteoporosis group (T≤-2.5) (Fig. 1).…”
Section: Participants and Study Designmentioning
confidence: 99%